THE DEVELOPMENT OFADMINISTRATIVE SYSTEM BASED MICROSOFT ACCESS 2016 (SIAMAR PONTREN) IN ISLAMIC BOARDINGSCHOOLAT MALANG CITY - Madziatul CHURIYAH (Fırat University, 2021)
This development and research aim to produce applications for archiving storage of incoming and outgoing mail. The name of the application is SIAMAR PONTREN. The research was conducted at Al-Ishlahiyah Islamic Boarding School, Malang City. The type of research method used is Research and Development. This research uses quantitative and qualitative data. Quantitative data were obtained from the results of media validation questionnaires and user trials. Qualitative data were obtained from suggestions and comments provided by media expert validators and users. The results of the evaluation of quantitative trials that have been managed show that 83% of the products are feasible to be tested. And 95% of the quantitative results show that the product is effective.